Using breeding and quantitative genetics to understand the C4 pathway. (8th November 2021) - Simpson, Conor J C; Reeves, Gregory; Tripathi, Anoop; Singh, Pallavi; Hibberd, Julian M
Abstract : We review literature relevant to forward genetics and consider when and how it could be applied to better understand C4 photosynthesis. Abstract: Reducing photorespiration in C3 crops could significantly increase rates of photosynthesis and yield. One method to achieve this would be to integrate C4 photosynthesis into C3 species. This objective is challenging as it involves engineering incompletely understood traits into C3 leaves, including complex changes to their biochemistry, cell biology, and anatomy. Quantitative genetics and selective breeding offer underexplored routes to identify regulators of these processes. We first review examples of natural intraspecific variation in C4 photosynthesis as well as the potential for hybridization between C3 and C4 species. We then discuss how quantitative genetic approaches including artificial selection and genome-wide association could be used to better understand the C4 syndrome and in so doing guide the engineering of the C4 pathway into C3 crops.